Knowledge of pediatrician on gastroesophageal reflux/gastroesophageal reflux disease in children: a preliminary study - Edward Surjono; Agus Firmansyah; Jose R. L. Batubara (Indonesian Pediatric Society, 2010)
Background Gastroesophageal reflux (OER) is involuntary movement of gastric content into esophagus due to transient lower esophageal sphincter relaxation. This condition usually ignored by physician. Many GER cases have severe complication before properly managed. Ten years after incorporating GER into Indonesia pediatric training curriculum, the knowledge of GER among pediatrician need to be measured.Objectives To measure pediatrician's knowledge of GER/GERD in children.Methods This was a cross sectional study using questionnaire and interview.Result There were 387 respondents who filled the questionnaire and being interviewed. The majority of respondents were between 25-45 years old (33.6%). Respondents who graduated before the year 2000 were 48.3%, and after 2000 were 51.7%. Majority of respondents were general pediatrician (90.2%) and 41.3% working in teaching hospitals Among pediatricians graduated after year 2000,6 6%,5 0.5% and 57.5% could gave more than 80% correct answer to questions about general knowledge, diagnosis and management of GERD as compared to 49.2%, 42.2% and 47% subjects graduated before year 2000. More pediatricians graduated before year 2000 answered the questions on general knowledge, diagnosis and management < 60% correctly compared to those graduated after year 2000 (42.2%, 25.2% and 28.3% vs. 14%,11.5% and 12%, respectively). Fifty five of 160 (34.4%) respondents who working in teaching hospital gave more than 80% correct answer to questions about GERD. Compared to those working in non-teaching hospitals, only 17.6% were able to correctly answer more than 80% of questions.Conclusions Better knowledge about GER/GERD are found among pediatricians graduated after the topics has been introduced to the curriculum and among those practicing in teaching hospitals.